2021
DOI: 10.1088/1742-6596/1933/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Application of Kahoot as Learning Media for Junior High School Students

Abstract: In today’s education world, we must use information technology in learning during this pandemic because learning during this pandemic period is carried out online. Meanwhile, many students and teachers must continue to adapt to new learning media with different methods. Currently, there are many designs for learning methods, one of which is gamification. Gamification is one way to make learning exciting and liked by students. This study designed learning media using the Kahoot tool, which contains multimedia e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Interviews and observations have shown that pupils in class 8 of junior high school (SMP) are not yet proficient in arts and culture courses and that traditional ways of learning, such as compiling pantomime texts, remain the most common. Due to the prevalence of online education during the Covid-19 epidemic, innovative teaching strategies-like gamification-are required to ensure students learn effectively and efficiently (Waworuntu & Suyoto, 2021). This editorial introduction discusses the benefits and difficulties that the rise of digital technology has brought to the field of media education.…”
Section: Methodsmentioning
confidence: 99%
“…Interviews and observations have shown that pupils in class 8 of junior high school (SMP) are not yet proficient in arts and culture courses and that traditional ways of learning, such as compiling pantomime texts, remain the most common. Due to the prevalence of online education during the Covid-19 epidemic, innovative teaching strategies-like gamification-are required to ensure students learn effectively and efficiently (Waworuntu & Suyoto, 2021). This editorial introduction discusses the benefits and difficulties that the rise of digital technology has brought to the field of media education.…”
Section: Methodsmentioning
confidence: 99%
“…175). Dengan demikian melalui motivasi peserta didik secara otomatis dapat mempengaruhi hasil didalam belajar, maka dalam hal ini indikator meningkatnya pemahaman siswa itu dapat terlihat melalui hasil atau perolehan belajar, oleh karena itu berikut peneliti sajikan berkenaan dengan pembahasan dari hasil wawancara yang telah peneliti lakukan (Waworuntu & Suyoto, 2021).…”
Section: Dampak Penerapan Aplikasi Kahootunclassified